P092 Punica Granatum affects gut biofilm-forming bacteria and promotes intestinal mucosal healing regulating the crosstalk between epithelial cells and intestinal fibroblasts. (30th January 2023) - Rizzo, G; Pineda Chavez, S E; Vandenkoornhuyse, E; Cardenas, C; Cento, V; Meanti, L; Roda, G; Loy, L; Dal Buono, A; Gabbiadini, R; Lovisa, S; Rusconi, R; et al.
Abstract: Background: Punica Granatum (PG), is a bioactive compound of Pomegranate exerting anti-inflammatory activities. Clinical studies have demonstrated an improvement of clinical response in inflammatory bowel diseases (IBD) patients when PG was taken as a complement to standard medications. However, the molecular mechanisms underlying its beneficial effects are still scarcely investigated. In this study, we assessed the effects of PG on bacterial biofilm formation, and we investigated the properties of the PG to promote mucosal wound healing. Methods: Bacterial biofilm formation was assessed using microfluidic devices for 24 or 48 hours. Acute colitis model was induced in C57BL/6N mice by 3% dextran sodium sulfate administration in their drinking water for 5 days. During the recovery phase of colitis, mice received saline or PG (200 mg/kg body weight) oral gavage for 11 days. . Colitis was scored daily evaluating the body weight loss, bleeding and consistency of stool. In vivo intestinal permeability was performed by fluorescein isothiocyanate-conjugated dextran assay, bacterial translocation by Fluorescence in situ hybridization on tissues, whereas epithelial and mucus integrity by immunostaining for JAM-A and MUC-2 markers. Primary fibroblasts, isolated from healthy and inflamed area of 6 IBD patients, and Caco-2 cells were stimulated with or without PG (15 ug/ml). Inflammatory mediators were measured at mRNA and protein levels by RT-PCR, WB or by Bio-plex multiplex immunoassay respectively. Results: Microfluidic experiments revealed beneficial effects of PG to inhibit biofilm formation of GRAM- bacteria and to promote the expansion of some intestinal commensal Gram+ bacteria. In vivo, PG boosted the recovery phase of colitis promoting a complete restoration of intestinal barrier with the regeneration of the mucus layer compared to saline group as also demonstrated by no traces of bacteria spread into the mucosa. The PG enriched crypt-associated fibroblasts. In vitro, inflamed fibroblasts responded to PG by down-regulating the release of metalloproteinases, IL-6, IL-8 and up-regulating the levels of HGF. Caco-2 cells cultured in medium supplemented with PG increased the expression of Sox-9 and CD44, whereas in the presence of HGF or when plated with fibroblast-conditioned medium displayed a decrease expression of Sox-9 and CD44 and increase of AXIN2, a negative regulator of Wnt signaling. Conclusion: These data provide new insight of the multiple effects of PG on promoting mucosal homeostasis in IBD by affecting biofilm formation of pathogens, promoting expansion of commensals and favoring the regeneration of intestinal barrier by regulating the crosstalk between epithelial cells and stromal cells.